Adult vaccination against tetanus and diphtheria: the European perspective. (12th July 2016) - Weinberger, B.
Summary: Besides immunizations against influenza, Streptococcus pneumoniae and herpes zoster, which are recommended specifically for elderly people, regular booster vaccinations against tetanus, diphtheria and in some cases pertussis and polio are recommended in many European countries for adults, including elderly people. Vaccination recommendations for adults differ greatly between individual countries and coverage data is scarce. Tetanus‐specific antibody concentrations are generally higher than diphtheria‐specific antibodies, and a substantial proportion of adults, and particularly of elderly people, do not have protective antibody concentrations against diphtheria. Antibody levels increase upon booster vaccination in all age groups, but diphtheria‐specific antibody concentrations remain below protective levels in some older individuals, even immediately after vaccination and long‐term protection is frequently not achieved. Future vaccination strategies should therefore include regular and well‐documented booster shots, e.g. against tetanus and diphtheria, throughout life.